2023
DOI: 10.1159/000533757
|View full text |Cite
|
Sign up to set email alerts
|

Fat Intake and Fat Quality in Pregnant and Lactating Women, Infants, Children, and Adolescents and Related Health Outcomes: A Scoping Review of Systematic Reviews of Prospective Studies

Bernadeta Patro-Golab,
Bartlomiej M. Zalewski,
Michael Kammermeier
et al.

Abstract: <b><i>Introduction:</i></b> Dietary fat intake during pregnancy and childhood is important for health. However, several health aspects are inconclusive. <b><i>Methods:</i></b> We systematically searched Medline, Cochrane Library, and Epistemonikos for systematic reviews (SRs) of randomized controlled trials (RCTs) and/or prospective cohort studies published from January 01, 2015, to December 31, 2019, assessing the association of dietary fat intake (including die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…By transitioning mothers from DEF to a DHA-supplemented diet, we can also test whether maternal DHA supplementation rescues the offspring phenotype. Given that pregnant and lactating women are advised to supplement with DHA to support fetal and infant growth and development (75), these experiments have excellent translational potential.…”
Section: Discussionmentioning
confidence: 99%
“…By transitioning mothers from DEF to a DHA-supplemented diet, we can also test whether maternal DHA supplementation rescues the offspring phenotype. Given that pregnant and lactating women are advised to supplement with DHA to support fetal and infant growth and development (75), these experiments have excellent translational potential.…”
Section: Discussionmentioning
confidence: 99%
“…Those mentioning supplementation either did not specify amounts [14] or referred to "women of low omega-3 FAs status" [24], raising questions on strategies to identify these. Importantly, recent systematic evidence summaries indicated that omega-3 FA supplementation during pregnancy is effective in reducing the risk of preterm birth [40,41]. In light of this evidence, future guideline developers may revisit current approach to omega-3 FA intake in prenatal period.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly, all guidelines identified by us that targeted infants and children also provided recommendations regarding PUFA intake, overall promoting consumption of foods rich in these FAs, as such in infancy, and as a substitute for SFA in later childhood. While clearly PUFA deficiency has detrimental health effects, the evidence for beneficial effects of higher versus lower dietary intake of PUFA or its supplementation, in particular during infancy, and in relation to various health outcomes (e.g., growth, neurological, visual, and cognitive outcomes, allergic diseases, or cardiovascular health) is mainly inconsistent [41]. Guidelines for children >2 years of age consistently focused on the avoidance of SFA and TFA intake, apparently reflecting the goal of reducing CVD risk in adulthood [9,44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation